The Comparative Analysis of Attendant Subdivision’s Formalized Cost Sharing Methods (Csm) - Kuzmenko, L. V.; Larka, M. I. (Miskolci Egyetem, 2007)
The comparative analysis of the formalized earlier by us methods of expenses distribution by criteria of exactness, labour – intensiveness and self-descriptiveness is executed. It is shown, that the two-stages method of the mutual distribution most precisely and in details describes process of expenses distribution of the attendant subdivisions, insignificantly conceding to the other methods by labour – intensiveness.